Long Run Relationship Between Exports, Imports and its Determinants of Medical Instruments: Case of Pakistan - Fazal-ur-Rehman (International Journal of Experiential Learning & Case Studies)
Medical instruments are the popular export products of Pakistan and retain their competitive edge in this f ield of medical instruments. After the review of literature, this study aims to check the existence of a long-run relationship between export of medical instruments and import of medical instruments, export promotion program and exchange rate index. The empirical analysis used the monthly time series data for June 2003 to December 2017 released by State Bank of Pakistan. The unit root results directed to apply the Johansen Cointegration test, and the result of this lead to Vector error correction estimate. The finding of this study reveals that there is a positive and signif icant long-run relationship between medical instruments export and import of medical goods and exchange rate index. The study has policy implications for medical instruments, sector stakeholders and the Government of Pakistan.